Pengenalan Citizen Jurnalism Bagi Guru dan Siswa Sebagai Media Publikasi Kegiatan Sekolah - Ahmadin; Najamuddin (Insan Kreasi Media, 2022)
This community service article discusses the importance of providing the basics of understanding and developing the ability to write news about school activities among teachers and students. As it is known that various school activities are an indicator of the implementation of work programs that are planned for both short-term annual and long-term in multi-year. The realization of the implementation of a number of school work programs should ideally be disseminated to the general public, so that the reputation of the educational institution concerned increases. This can be done at least if the school has at least two things, namely among teachers or students who have the ability to write news at least, namely the Citizen Journalism model and open collaboration networks or partnerships with print and online mass media. From this premise, it is important to carry out a series of socialization activities through training activities for both teachers and students. This activity starts from identifying the lack of socialization of school activities because of the lack of publicity, conducting institutional collaboration between campuses and schools, and improving the ability to write news about school activities.